2017
DOI: 10.1371/journal.pone.0185776
|View full text |Cite
|
Sign up to set email alerts
|

Ciguatoxicity of Gambierdiscus and Fukuyoa species from the Caribbean and Gulf of Mexico

Abstract: Dinoflagellate species belonging to the genera Gambierdiscus and Fukuyoa produce ciguatoxins (CTXs), potent neurotoxins that concentrate in fish causing ciguatera fish poisoning (CFP) in humans. While the structures and toxicities of ciguatoxins isolated from fish in the Pacific and Caribbean are known, there are few data on the variation in toxicity between and among species of Gambierdiscus and Fukuyoa. Quantifying the differences in species-specific toxicity is especially important to developing an effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
135
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 110 publications
(147 citation statements)
references
References 77 publications
(92 reference statements)
10
135
1
1
Order By: Relevance
“…Furthermore, 10 other C-CTX analogues or isomers with different mass have also been isolated [16], but their structures have not yet been elucidated. The structure of the toxin precursors at producers (trophic level 1) in the Caribbean has not yet been confirmed, although CTX-like activity was demonstrated by biological cytotoxicity assay in species including G. carolinianus or G. excentricus and ranged from 0.02 to 469 fg CTX3C (aka P-CTX3C) equivalents per cell [21]. In contrast, marine first-order consumers (trophic level 2) of the Caribbean region have never been analyzed for their CTX contents.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, 10 other C-CTX analogues or isomers with different mass have also been isolated [16], but their structures have not yet been elucidated. The structure of the toxin precursors at producers (trophic level 1) in the Caribbean has not yet been confirmed, although CTX-like activity was demonstrated by biological cytotoxicity assay in species including G. carolinianus or G. excentricus and ranged from 0.02 to 469 fg CTX3C (aka P-CTX3C) equivalents per cell [21]. In contrast, marine first-order consumers (trophic level 2) of the Caribbean region have never been analyzed for their CTX contents.…”
Section: Introductionmentioning
confidence: 99%
“…, Litaker et al. ). Several of those studies have shown that G. excentricus and G. silvae are the most toxic species in the Caribbean and eastern Atlantic (Fraga et al.…”
Section: Average Toxicity Estimates For Gambierdiscus Excentricus Andmentioning
confidence: 99%
“…The G. excentricus isolates were obtained from samples collected at Pulley Ridge reef (N 25°53.131, W 83°36.368; Pulley Ridge Gam2 = Pulleys Ridge in Litaker et al. , Pisapia et al. ) located 160 km west of the Tortugas Ecological Reserve in the Northeastern Gulf of Mexico and from the Bahamas (N 26°38.849, W 78°04.839; Bahamas Gam5 = BahamaGam5 in Litaker et al.…”
Section: Average Toxicity Estimates For Gambierdiscus Excentricus Andmentioning
confidence: 99%
See 2 more Smart Citations